REGIME SHIFTS IN ARCTIC OSCILLATION (AO) VARIABILITY 1951–2009 - Marosz, Michał (Bulletin of Geography. Physical Geography Series, 2010)
Arctic Oscillation (AO) reflects the dominating mode of SLP (or 1000hPa) variability in hemispheric scale and seems to bear an effect on the weather and, in longer time scales, on climate. The aim of the research was to identify the possible regime shifts in the multiannual course of AO index which in turn might be utilised in the identification and quantification of the regional/local meteorological field response. The data (AO monthly and daily index values) were acquired from the NOAA Climate Prediction Centre. The AO index is constructed by projecting monthly/daily anomalies of 1000hPa heights poleward of 20°N onto the loading pattern of the AO – 1st (leading) EOF of the 1000hPa height field for the same spatial domain. The temporal scope of analysis was 1951–2009. The analysis comprised the regime shift identification techniques that track the shifts in the mean values and in the magnitude of fluctuations as well as the usage of the classical linear trend identification in the annual and seasonal scale. The regime shift recognition was followed by the compositing method that allowed the analysis of spatial anomalies in SLP field in Euro-Atlantic region that reflect the response of the regional airflow to identified circulation regimes.